Epidemiology and treatment of mucormycosis. (September 2013) - Lewis, Russell E; Kontoyiannis, Dimitrios P
Mucormycosis is an uncommon but aggressive opportunistic fungal infection that afflicts patients with severe underlying immunosuppression, uncontrolled hyperglycemia and/or ketoacidosis, patients with iron overload resulting from frequent blood transfusions or blood disorders and occasionally healthy patients who are inoculated with fungal spores through traumatic injuries. The clinical presentation of mucormycosis is initially indistinguishable from other common infections, and if not diagnosed early and aggressively treated, it is almost always fatal. In this article we summarize recent changes in the epidemiology of mucormycosis, discuss diagnostic and clinical clues suggestive of the infection and provide a general strategy for managing the infection in the absence of data from well-controlled, prospective clinical trials.